A Suggestion of a Procedural Method for the Management of Post-War Waste - Aws S. Noaman; Angham E. Alsaffar (Civil Engineering Journal, 2019)
The increasing number of disasters (natural or man-made) worldwide has made post-disaster waste management an essential aspect of disaster recovery. This is obvious in Iraq where the Iraqi government faces an important challenge regarding the events of 2014 (ISIS gang conflict) and the accumulation of huge volumes of construction and demolition (C&D) waste resulting from military operations and terrorist destruction. Field surveys by the specialist teams estimated the amount of waste at about 10 million tons in the Nineveh governorate only, much of which comprises potentially useful materials that could be reused or recycled in the reconstruction process. This paper investigates the obstacles to the sustainable management of such waste in the Nineveh governorate. A pilot questionnaire survey of 76 experts working in the waste management sector was carried out to identify the obstacles to the sustainable management of accumulated waste in the Nineveh governorate. Data analysis was carried out using SPSS version 23.0. Based on the identified obstacles, a procedural method of managing post-war waste that accumulated in Iraq has been created. The paper illustrates several conclusions in the strategic, economic, social, and environmental sectors to address identified gaps in sustainable waste management in Iraq. It is hoped that this study’s results will support post-disaster sustainable development goals in Iraq.